2009
DOI: 10.1097/ta.0b013e31817e611d
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Penetrating Injuries of the Pharynx and Esophagus in the Severely Injured Patient

Abstract: Radiologic studies should not be used for pharyngeal injuries. Although radiologic studies accurately diagnosed penetrating injuries of the esophagus, it is not as expeditious as videoendoscopy performed by the trauma surgeon. Videoendoscopy should be part of the trauma surgeons' armamentarium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 9 publications
1
30
0
1
Order By: Relevance
“…It has been demonstrated that contrast swallow studies are less sensitive in detecting hypopharyngeal injuries as compared with esophageal injury and flexible nasoendoscopy or video endoscopy should be part of the ''trauma surgeon's armamentarium.'' 51,53 …”
Section: Annotated Text For the Algorithmmentioning
confidence: 98%
“…It has been demonstrated that contrast swallow studies are less sensitive in detecting hypopharyngeal injuries as compared with esophageal injury and flexible nasoendoscopy or video endoscopy should be part of the ''trauma surgeon's armamentarium.'' 51,53 …”
Section: Annotated Text For the Algorithmmentioning
confidence: 98%
“…The quoted sensitivity of a contrast swallow ranges from 48 to 100%, with poorer results for higher lesions including the hypopharynx 38,39 . Flexible or rigid oesophagoscopy has better accuracy for these higher lesions with a sensitivity of up to 100% 39,40 . In addition, direct oesophagoscopy is less technically challenging to perform than a contrast swallow in patients who are intubated and can also be undertaken in unstable patients or performed intra‐operatively.…”
Section: Investigation Into Suspected Pharyngo‐oesophageal Injurymentioning
confidence: 99%
“…38,39 Flexible or rigid oesophagoscopy has better accuracy for these higher lesions with a sensitivity of up to 100%. 39,40 In addition, direct oesophagoscopy is less technically challenging to perform than a contrast swallow in patients who are intubated and can also be undertaken in unstable patients or performed intra-operatively. One advantage of a contrast swallow over oesophagoscopy, however, is that the size and extent of a pharyngeal or oesophageal leak can be assessed; this information has been used in some centres to determine how oesophageal injuries are managed.…”
Section: Investigation Into Suspected Pharyngo-oesophageal Injurymentioning
confidence: 99%
“…If there is any suspicion of hypopharyngeal or esophageal injury such as in penetrating injuries to the neck or torso, contrasted radiologic studies and endo- scopy are indicated. Fiberoptic endoscopic examination is the best screening tool for recognition of a possible hypopharyngeal mucosal violation, and is necessary if suspicion is high, as contrasted radiologic studies frequently miss hypopharyngeal injuries [4][5][6]. Endoscopic examination will also reveal the exact size and location of the injury, which is necessary to determine further workup and management.…”
Section: Discussionmentioning
confidence: 99%